The Role of Education in Preventing Bullying: A Psychological Approach in Elementary Schools - Khairunnisa Ulfadhilah; Salsabila Dwi Nurkhafifah (Sekolah Tinggi Agama Islam Solok Nan Indah, 2025)
Bullying in school settings remains an issue that requires serious attention due to its impact on students' psychological well-being and social development. Therefore, this study aims to explore the role of education in preventing bullying and understand how educators, students and parents respond to this phenomenon. This study used qualitative methods to explore the experiences and perspectives of educators, students and parents regarding the phenomenon of bullying. Through in-depth interviews and focus group discussions, this study found that education is an important pillar in creating a safe school environment that supports students' emotional development. Educators play a role in providing students with an understanding of the negative impact of bullying, as well as teaching empathy and social skills needed to build peer relationships. In addition, psychological interventions, such as counseling and character development programs, contribute to raising students' awareness of bullying behaviors and the importance of mutual respect. This study shows that parental involvement is also very important in supporting anti-bullying education by building good communication at home. The results of this research conducted by elementary schools are expected to provide recommendations for schools to design a more inclusive curriculum and create policies that support bullying prevention, so that students can learn in a safe, comfortable and positive environment. Thus, education not only serves to transfer knowledge, but also shapes character and social values that can prevent bullying behavior among students.